2017
DOI: 10.1016/j.neuropsychologia.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Neural signatures of second language learning and control

Abstract: Experience with multiple languages has unique effects on cortical structure and information processing. Differences in gray matter density and patterns of cortical activation are observed in lifelong bilinguals compared to monolinguals as a result of their experience managing interference across languages. Monolinguals who acquire a second language later in life begin to encounter the same type of linguistic interference as bilinguals, but with a different pre-existing language architecture. The current study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 70 publications
(83 reference statements)
1
8
0
Order By: Relevance
“…Here, we examine a more complex form of sleep encoding, namely rapid implicit relational binding of vocabulary, which is called paired-associates learning in the psychological literature. Paired-associates learning draws on the episodic memory system [19,20], which critically depends upon the hippocampus. In humans, hippocampus-assisted relational learning is generally believed to require consciousness during encoding [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we examine a more complex form of sleep encoding, namely rapid implicit relational binding of vocabulary, which is called paired-associates learning in the psychological literature. Paired-associates learning draws on the episodic memory system [19,20], which critically depends upon the hippocampus. In humans, hippocampus-assisted relational learning is generally believed to require consciousness during encoding [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Bartolotti, Bradley, Hernandez, and Marian () demonstrated how one's experience with multiple languages might have unique effects on the cortical structure and information processing. Specifically, differences in gray matter density and patterns of cortical activation were observed in lifelong bilinguals as a result of their experiences managing interference across languages when compared to those in monolinguals.…”
Section: Resultsmentioning
confidence: 99%
“…This preliminary search returned a total of 1448 results. Three additional studies were identified through other resources (i.e., Hanulovà et al, 2011;Tanner et al, 2014;Bartolotti et al, 2017) yielding a total of 1451 results. Duplicates were removed from this initial set leading to a total of 739 results.…”
Section: Data Collection and Preparationmentioning
confidence: 99%